2018
DOI: 10.1002/stem.2858
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Aniridia-Related Keratopathy by CRISPR/Cas9 Genome Editing of Human Limbal Epithelial Cells and Rescue by Recombinant PAX6 Protein

Abstract: Heterozygous PAX6 gene mutations leading to haploinsufficiency are the main cause of congenital aniridia, a rare and progressive panocular disease characterized by reduced visual acuity. Up to 90% of patients suffer from aniridia-related keratopathy (ARK), caused by a combination of factors including limbal epithelial stem cell (LSC) deficiency, impaired healing response and abnormal differentiation of the corneal epithelium. It usually begins in the first decade of life, resulting in recurrent corneal erosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…PAX6 transcription factor is known to be the master gene of eye formation (for review, Shaham et al, 2012). Previous studies reported that in the context of Pax6 mutation, corneal cells were unable to differentiate properly, and adopt the corneal epithelial cell identity (Roux et al, 2018). After Pax6a expression was validated by qPCR in control and wounded corneas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PAX6 transcription factor is known to be the master gene of eye formation (for review, Shaham et al, 2012). Previous studies reported that in the context of Pax6 mutation, corneal cells were unable to differentiate properly, and adopt the corneal epithelial cell identity (Roux et al, 2018). After Pax6a expression was validated by qPCR in control and wounded corneas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LSC deficiency is the underlying mechanism responsible for cornea opacification and ultimately blindness in aniridia. [57][58][59][60] Hence, in future studies, we aim to deliver our CRISPR strategy to LSCs of post-weaned Fey mice to model gene therapy in recently diagnosed children with aniridia.…”
Section: Discussionmentioning
confidence: 99%
“…This consequence might due to metabolic abnormalities of the ocular surface caused by haploinsufficiency of PAX 6 . 17 Studies demonstrated the individuals harbouring PAX 6 mutation displayed various clinical symptoms, including aniridia, keratitis, cataract, lens dislocation, ciliary body hypoplasia, foveal hypoplasia and brain structure abnormalities. In this study, nystagmus, ptosis, glaucoma, corneal pannus and other abnormalities were observed, and OCT showed that all affected individual had foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%